Violence against women migrant workers in Thailand: A cross-sectional study on experiences, impact, and help seeking - Montakarn Chuemchit; Nyan Linn; Chit Pyae Pyae Han; Zayar Lynn; Suttharuethai Chernkwanma; Nutta Taneepanichskul; Wandee Sirichokchatchawan; Ratana Somrongthong (PLoS ONE, 2026)
Background Violence against women migrant workers is an alarming public health problem. This study aims to investigate the experiences and impact of violence on women migrant workers in Thailand, including their help-seeking patterns, knowledge, future plans for seeking help, ways of help received, and the factors associated with violence. Methods This cross-sectional study included 494 women migrant workers across seven key provinces in Thailand – Bangkok, Chiang Rai, Chonburi, Samut Prakan, Rayong, Samut Sakhon, and Tak. Data was collected by well-trained enumerators using the validated standardized structured questionnaire. We analysed multiple logistic regressions to investigate the factors associated with experiences of violence and adjusted odds ratios (AOR) with a 95% CI were presented. Results The study identified the lifetime prevalence of violence to be 54.45%, 42.47% for intimate partner violence (IPV), and 46.15% for non-intimate partner violence (N-IPV). Women experienced psychological, physical, and occupational impacts from violence. A significant proportion of women sought informal support from friends (59.1%) and family (52.6%), while formal support was most commonly sought from employers (15.3%) and the police (6.6%). Factors associated with IPV and/or N-IPV among women migrant workers included area of residence, duration of stay, monthly income, perceived safety, Thai language proficiency, and job or income loss during the COVID-19 pandemic. Conclusion The findings highlight widespread violence against migrant women workers in Thailand, urging the need for tailored support services. Key strategies include strengthening workplace-based protections, multilingual reporting mechanisms, peer networks, culturally relevant education, and individual- and community-level interventions within labour, health, and social protection systems. Collaborative efforts among policymakers and stakeholders are vital for the prevention of and response to violence and for ensuring the safety of women migrant workers.